THE EFFECTIVENESS OF WEB KITARA IN IMPROVING ARABIC VOCABULARY WRITING SKILLS FOR BEGINNERS - Muhammad Kesit Barnabila; Muhammad Hasbi Annahiri; Taufik Taufik; M. Baihaqi; Muhammad Fajar Tubagus Dewantara (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study aims to examine the effectiveness of the interactive web-based learning media, WEB KITARA, in improving Arabic vocabulary writing skills among beginner-level elementary students. A mixed-methods design with a quasi-experimental approach was used. The study involved two classes: Al-Aziz as the intervention group and Al-Mu’min as the control group. Data were collected through an Arabic vocabulary writing test, interviews with teachers and students, and qualitative thematic analysis. Results showed a statistically significant difference between the groups, with students using WEB KITARA achieving higher average scores and more consistent learning outcomes. Qualitative findings indicated increased motivation, active participation, and learning satisfaction due to the platform’s interactive writing features. The study concludes that systematic integration of WEB KITARA effectively enhances Arabic vocabulary and writing skills and creates a more engaging learning environment for beginner learners. This media is recommended as an innovative and practical tool for teaching Arabic in Islamic elementary schools.